Application of the Six Sigma methodology in the evaluation of the results in Cell Blood Count EQAS Program (PNAEQ) - Ovelheiro, Ana (2019)
Introduction: The haemogram is one of the most frequently requested laboratory tests, in hospital and ambulatory. Therefore, given its importance in the clinical context, an evaluation was performed on the results of the clinical laboratories participating in PNAEQ’s EQA Cell Blood program. The main objective of this work was to improve the Sigma quality level of the clinical laboratories and reduce the variability of their results.